A label-free electrochemical DNA biosensor used a printed circuit board gold electrode (PCBGE) to detect SARS-CoV-2 without amplification. Issue 6 (14th February 2023) - Zambry, Nor Syafirah; Awang, Mohd Syafiq; Beh, Khi Khim; Hamzah, Hairul Hisham; Bustami, Yazmin; Obande, Godwin Attah; Khalid, Muhammad Fazli; Ozsoz, Mehmet; Manaf, Asrulnizam Abd; Aziah, Ismail
Abstract : The graphical representation depicts a novel method of detecting the SARS-CoV-2 N gene without amplification using a label-free electrochemical DNA biosensor-based printed circuit board gold electrode (PCBGE). Abstract : The emergence of coronavirus disease 2019 (COVID-19) motivates continuous efforts to develop robust and accurate diagnostic tests to detect severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Detection of viral nucleic acids provides the highest sensitivity and selectivity for diagnosing early and asymptomatic infection because the human immune system may not be active at this stage. Therefore, this work aims to develop a label-free electrochemical DNA biosensor for SARS-CoV-2 detection using a printed circuit board-based gold substrate (PCBGE). The developed sensor used the nucleocapsid phosphoprotein (N) gene as a biomarker. The DNA sensor-based PCBGE was fabricated by self-assembling a thiolated single-stranded DNA (ssDNA) probe onto an Au surface, which performed as the working electrode (WE). The Au surface was then treated with 6-mercapto-1-hexanol (MCH) before detecting the target N gene to produce a well-oriented arrangement of the immobilized ssDNA chains. The successful fabrication of the biosensor was characterized using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and atomic force microscopy (AFM). The DNA biosensor performances were evaluated using a synthetic SARS-CoV-2 genome and 20 clinical RNA samples from healthy and infected individuals through EIS. The developed DNA biosensor can detect as low as 1 copy per μL of the N gene within 5 minutes with a LOD of 0.50 μM. Interestingly, the proposed DNA sensor could distinguish the expression of SARS-CoV-2 RNA in a patient diagnosed with COVID-19 without any amplification technique. We believe that the proposed DNA sensor platform is a promising point-of-care (POC) device for COVID-19 viral infection since it offers a rapid detection time with a simple design and workflow detection system, as well as an affordable diagnostic assay.